Evaluasi Program Pengembangan Industri Kecil dan Menengah Pada Pengrajin Tahu di Kelurahan Lopang Kecamatan Serang Kota Serang - Cynthia Utami Damayanti; Leo Agustino; Ima Maisaroh (Epistemik: Indonesian Journal of Social and Political Science, 2023)
This research focuses on the development program of the tofu industry sector in Lopang Village. One of the problems examined in this study is the lack of desire of tofu craftsmen in Lopang Village to attend training held by the Office of Cooperatives, SMEs, Industry and Trade of Serang City. This research aims to measure the success of the Small and Medium Industry Development Program (Case Study of Tofu Craftsmen in Lopang Village) using the CIPP theory by Daniel Stufflebeam (2003). This research uses descriptive qualitative methods by analyzing the results of interviews, observations, interviews, documentation and document studies. The results of this study indicate that based on the program evaluation proposed by Stufflebeam (2003), the SME development program case study of tofu craftsmen in Lopang Village has not fully achieved the objectives of the program caused by various factors. Overall, the existence of this program has not been able to increase the income of Lopang Village tofu craftsmen even though there have been changes in the packaging of tofu.